Cvd synthesis of intermediate state-free, large-area and continuous mos2 via single-step vapor-phase sulfurization of moo2 precursor - Chiawchan, Tinna; Ramamoorthy, Harihara; Buapan, Kanokwan; Somphonsane, Ratchanok (My University, 2021)
The low evaporation temperature and carcinogen classification of commonly used molybdenum trioxide (MoO3) precursor render it unsuitable for the safe and practical synthesis of molybdenum disulfide (MoS2). Furthermore, as evidenced by several experimental findings, the associated reaction constitutes a multistep process prone to the formation of uncontrolled amounts of intermediate MoS2−yOy phase mixed with the MoS2 crystals. Here, molybdenum dioxide (MoO2), a chemically more stable and safer oxide than MoO3, was utilized to successfully grow cm-scale continuous films of monolayer MoS2. A high-resolution optical image stitching approach and Raman line mapping were used to confirm the composition and homogeneity of the material grown across the substrate. A detailed examination of the surface morphology of the continuous film revealed that, as the gas flow rate increased by an order of magnitude, the grain-boundary separation dramatically reduced, implying a transition from a kinetically to thermodynamically controlled growth. Importantly, the single-step vapor-phase sulfurization (VPS) reaction of MoO2 was shown to suppress intermediate state formations for a wide range of experimental parameters investigated and is completely absent, provided that the global S:Mo loading ratio is set higher than the stoichiometric ratio of 3:1 required by the VPS reaction.
Keywords: 2D materials; Chemical vapor deposition; Monolayer MoS2; MoO2 precursors; Raman